The scientific career path of Alexander Tartagnus in the context of university life in the 15th century - Szymańska, Aleksandra (The Opole Studies in Administration and Law, 2017)
Alexander Tartagnus, considered to be one of the last great representatives of the school of commentators, was also a defender of writing in Latin, which was the language of medieval scholarship. His life is an example of a harmonious combination of academic activities and legal practice, which was most fully manifested in the form of legal advice. His knowledge was used both by judges to assist them in resolving contentious issues and by parties who wanted to better understand their legal position. During his life he wrote seven books of consilia, which established his place among the authors contributing to the development of ius commune. The objective of this article is to present the biography of Alexander Tartagnus, which enlightens the reader not only about this single Bologna master, but also enriches their knowledge of the environment in which he had lived and worked.